BIOCERAMICS IN ENDODONTICS - A REVIEW - Srinidhi Surya RAGHAVENDRA; Ganesh Ranganath JADHAV; Kinjal Mahesh GATHANI; Pratik KOTADIA (Istanbul University, 2017)
Bioceramics are materials which include Alumina, Zirconia, Bioactive glass, Glass ceramics, Hydroxyapatite, resorbable Calcium phosphates, among others. They have been used in dentistry for filling up bony defects, root repair materials, apical fill materials, perforation sealing, as endodontic sealers and as aids in regeneration. They have certain advantages like biocompatibility, non toxicity, dimensional stability and most importantly in endodontic applications, being bio-inert. They have a similarity to Hydroxyapatite, an intrinsic osteo conductive activity and have an ability to induce regenerative responses in the human body. In Endodontics, they can be broadly classified into Calcium Phosphate/ Tricalcium/ Hydroxyapatite based, Calcium Silicate based or mixtures of Calcium Silicate and Phosphates. This review focuses on an overview of Bioceramics, classification and their advantages. It also gives a detailed insight into individual bioceramic materials currently used in the fields of Endodontics along with their properties and applications.